(untitled) (Baghdad Science Journal, 2025)
The experiment was carried out to study the effect of two concentrations of NPK 0.25 and 0.50g/kg soil on some physiological characters of Petroselinum hortense. The results showed increased dry weight, absolute growth rate (AGR) relative growth rate (RGR) and percentage of N,P and K in the plant. The differences in studied plant characters were significant in the case of the first concentration compared with the second one.